Epidemiology of GB virus type C among patients infected with HIV in Singapore. Issue 5 (31st January 2014) - Lee, Chun Kiat; Tang, Julian Wei‐Tze; Chiu, Lily; Loh, Tze Ping; Olszyna, Dariusz; Chew, Nicholas; Archuleta, Sophia; Koay, Evelyn Siew‐Chuan
<x xml:space="preserve">Abstract</x> Several studies have shown that individuals co‐infected with GB virus type C (GBV‐C), and human immunodeficiency virus (HIV) have slower progression to acquired immunodeficiency syndrome (AIDS) and a prolonged lifespan, compared to those infected with only HIV. In Singapore, despite the steadily increasing number of HIV infections in recent years, there are no studies documenting the extent of GBV‐C/HIV co‐infection in this group of patients. To fill this dearth of information, two GBV‐C screening assays was performed on 80 archived HIV‐1‐positive samples from the National University Hospital. The overall prevalence of GBV‐C co‐infection among patients infected with HIV in this study was 10% (8/80). Phylogenetic analysis of the eight dual‐infection cases revealed that genotypes 3 (4/8, 50%) and 2a (2/8, 25%) were the main genotypes circulating among these Singaporean HIV patients. One case each of genotypes 2b (1/8, 12.5%) and 4 (1/8, 12.5%), which have not been described previously in Singapore, were identified. These findings hint at the complex epidemiology of GBV‐C in different patient groups and a larger study would be needed to characterize, and understand the potential clinical impact of GBV‐C co‐infection on the patients. J. Med. Virol. 86:737–744, 2014. © 2014 Wiley Periodicals, Inc.